Clinical intensive care medicine : Vol.1 - Gomez, Carlos M. H. (Introductory series in medicine ;, 2015)
Intensive care patients are the most critically ill in any hospital and they are a patient group that utilises a disproportionate amount of medical resources. Intensive care medicine, around for about 40 years, is a relatively recent but globally expanding specialty due to a growing geriartric population of discerning demand for health system. The older generation of intensivists are approaching retirement. The middle generation is trained in various medical specialties and then subspecialised in intensive care. These doctors now lead the way in clinical practice, research, management and training. On the other hand, the younger generation of intensivists includes an ever increasing number of doctors who, for the first time, enjoy a structured training program with clinical rotations, courses, and exam qualifications. Written by outstanding specialist practitioners who are also internationally acclaimed authors from the UK and North America, this is an authoritative guide to practical intensive care medicine. The clinical contents of the book share a practical and educational common thread with each chapter addressing pertinent clinical challenges comprehensively. This invaluable book is specially targeted at medical students, trainees in intensive care medicine and other acute specialties, consultants wishing to remain up to date on all branches of this vast specialty and other allied professionals practicing in intensive care including nurses and physiotherapists.